2020
DOI: 10.7759/cureus.10736
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Perinatal Depression: An Updated Literature Review

Abstract: The objective of this review was to determine if there is an association between maternal obesity and increased risk of perinatal depression. Original research articles were found by conducting an electronic database search of PubMed, ClinicalKey, PsycINFO, and Cochrane Library. Seven articles, published in the last five years, were reviewed. Of the seven articles, five demonstrated an association between some level of maternal obesity and increased risk of perinatal depressive symptoms. The two remaining arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…To this end, a multivariate modelling approach was employed wherein the resultant crude model was adjusted for covariates. Six covariates were selected based on their availability and clinical importance to depression based on previous literature [ 39 , 40 , 41 , 42 , 43 , 44 ]. Covariates included pre-pregnancy body mass index (BMI, kg/m 2 ), pre-pregnancy smoking status, maternal age, household income, mid-pregnancy perceived stress scores, and mid-pregnancy anxiety scores.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, a multivariate modelling approach was employed wherein the resultant crude model was adjusted for covariates. Six covariates were selected based on their availability and clinical importance to depression based on previous literature [ 39 , 40 , 41 , 42 , 43 , 44 ]. Covariates included pre-pregnancy body mass index (BMI, kg/m 2 ), pre-pregnancy smoking status, maternal age, household income, mid-pregnancy perceived stress scores, and mid-pregnancy anxiety scores.…”
Section: Resultsmentioning
confidence: 99%
“…Among putative mechanisms involved in the association between obesity and perinatal depression (PD), the alteration of hypothalamic-pituitary-adrenal (HPA) axis, observed in both obesity and depression, the increase of circulating glucocorticoids, higher levels of inflammation with related serum markers (including specific cytokines), oxidative stress, microbiome and psychological issues related to the changes of body-images, are widely discussed in the literature [6][7][8]. Pavlik and Rosculet [9], in their updated review of literature, discussed that overall evidences from studies conducted within 2020 have shown that obesity in association with its comorbidity may have a possible impact on the development of perinatal depressive symptoms: they reported findings from 5 studies confirming association between obesity and PD and 2 concluding there may be an impact of obesity on the general outcome of pregnancy but not on depressive maternal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity is also associated with problems initiating breastfeeding, with decreased suckling-induced secretion of prolactin, the key hormone required for milk production, and, on average, a shorter duration of breastfeeding. [5][6][7][8] Furthermore, women with maternal obesity have an increased incidence of postpartum depression, 9,10 which is well known to negatively impact on mother-child bonding. Longterm effects of maternal obesity include increased risk of dysregulation of metabolic and cardiovascular function in offspring.…”
Section: Introductionmentioning
confidence: 99%